Three-dimensional macroporous oxygen reduction catalyst and preparation method and application thereof

CN117476953BActive Publication Date: 2026-10-16FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210852205.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-20
Publication Date
2026-10-16
Estimated Expiration
2042-07-20

AI Technical Summary

Technical Problem

ZIF-8基材料仅存在微孔结构,氧气无法在高电解质浓度的电池催化电极内部快速传输质,通常只有催化剂表面的活性位能够参与催化反应过程,其内部深埋的活性中心难以参与氧还原催化反应,导致催化活性位利用率低

Benefits of technology

[0060] 1) The three-dimensional macroporous redox catalyst provided in this application exhibits excellent oxygen reduction performance, with an oxygen reduction half-wave potential of 0.901 V in 0.1 mol/L potassium hydroxide solution and an oxygen reduction mottled potential of 0.806 V in 0.5 mol/L sulfuric acid solution. Compared to noble metal catalysts, this oxygen reduction catalyst is a non-noble metal oxygen reduction catalyst, which reduces costs while exhibiting catalytic performance comparable to that of noble metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117476953B_ABST
    Figure CN117476953B_ABST
Patent Text Reader

Abstract

The application discloses a three-dimensional macroporous oxygen reduction catalyst and a preparation method and application thereof, and comprises a porous carbon material and an active component, wherein the active component is loaded on the porous carbon material, the active component comprises an active element, the active element comprises iron and cobalt, the iron and the cobalt are both atomically dispersed, and the catalyst has a micromorphology of a porous cobblestone structure. The oxygen reduction catalyst has excellent oxygen reduction performance, the oxygen reduction half-wave potential in a 0.1 mol / L potassium hydroxide solution is 0.901 V, and the oxygen reduction half-wave potential in a 0.5 mol / L sulfuric acid solution is 0.806 V. Compared with a noble metal catalyst, the oxygen reduction catalyst is a non-noble metal oxygen reduction catalyst, and the catalyst has a cost reduction and also has a catalytic performance not inferior to that of the noble metal catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a three-dimensional macroporous oxygen reduction catalyst, its preparation method, and its application, belonging to the field of new energy catalyst technology. Background Technology

[0002] Due to the high cost of precious metal catalysts, developing non-precious metal-based oxygen reduction reaction (ORR) catalysts is a crucial approach to achieving large-scale applications in metal-air batteries and proton exchange membrane fuel cells, considering both production cost reduction and the conservation of rare and precious metal resources. Metal-nitrogen-carbon structures exhibit excellent ORR catalytic activity under both acidic and alkaline conditions. A key research focus in this field is how to more effectively load metal-nitrogen active sites onto carbon supports while simultaneously enhancing the oxygen mass transfer rate on the support surface.

[0003] Metal-organic frameworks (MOFs) possess advantages such as high porosity and large specific surface area, showing great promise for applications in catalysis, energy storage, and separation analysis. Doping ZIF-8 with small amounts of metal elements during its synthesis can form well-dispersed metal-nitrogen coordination structures. However, ZIF-8-based materials exhibit only a microporous structure, hindering the rapid transport of oxygen within the high electrolyte concentration of the battery catalytic electrode. Typically, only active sites on the catalyst surface participate in the catalytic reaction, while deeply embedded active sites within the catalyst are unlikely to participate in oxygen reduction catalysis, resulting in low utilization of catalytic active sites. Summary of the Invention

[0004] To improve the utilization efficiency of catalytic active sites, this application constructs a three-dimensional porous structure in a metal-organic framework compound (ZIF-8) to enhance the utilization efficiency of catalyst active sites and improve the mass transfer rate of reaction substrates and catalytic products at the electrode interface.

[0005] According to one aspect of this application, a three-dimensional macroporous redox catalyst is provided, comprising a porous carbon material and an active component, wherein the active component is supported on the porous carbon material, and wherein the active component comprises active elements, including iron and cobalt, wherein both iron and cobalt are atomically dispersed, and the catalyst has a porous pebble-like structure. The catalyst of this application contains elements such as iron, cobalt, nitrogen, and carbon.

[0006] Optionally, in the catalyst, the mass fraction of iron is 0.1% to 5%, and the mass of iron is expressed as the mass of iron element.

[0007] Optionally, in the catalyst, the mass fraction of iron is 1% to 2%, and the mass of iron is expressed as the mass of iron element.

[0008] Optionally, in the catalyst, the mass fraction of cobalt is 0.1% to 5%, and the mass of cobalt is expressed as the mass of cobalt element.

[0009] Optionally, in the catalyst, the mass fraction of cobalt is 0.5% to 1.5%, and the mass of cobalt is based on the mass of cobalt elemental.

[0010] Optionally, the particle size of the catalyst is 2.0 to 3.0 μm.

[0011] Optionally, the porous carbon material includes nitrogen and carbon.

[0012] According to another aspect of this application, a method for preparing a three-dimensional macroporous redox catalyst is provided, comprising the following steps:

[0013] (a) Polymerize a mixture containing styrene, an initiator and a stabilizer to obtain a polystyrene spherical emulsion;

[0014] (b) The polystyrene ball emulsion, zinc salt and dimethylimidazole obtained in step (a) are mixed, reacted and centrifuged to obtain a metal-organic framework compound loaded with polystyrene balls. The compound is then washed with a washing solvent and dried to obtain a precursor powder.

[0015] (c) The precursor powder obtained in step (b) is added to an organic solution containing iron salt and cobalt salt, impregnated, and calcined to obtain the catalyst.

[0016] Optionally, the initiator is selected from at least one of potassium persulfate, sodium persulfate, and ammonium persulfate.

[0017] Optionally, the stabilizer is selected from at least one of polyvinylpyrrolidone, polyacrylic acid, and nonionic cellulose.

[0018] Optionally, the organic solvent is selected from at least one of methanol, ethanol, and cyclohexane.

[0019] Optionally, the washing solvent is selected from at least one of dimethylformamide and tetrahydrofuran.

[0020] Optionally, the zinc salt is selected from zinc nitrate and zinc acetate.

[0021] Optionally, the iron salt is a soluble iron salt.

[0022] Optionally, the iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric sulfate, and ferric acetylacetone.

[0023] Optionally, the iron salt is ferric nitrate.

[0024] Optionally, the cobalt salt is a soluble cobalt salt.

[0025] Optionally, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetylacetonate.

[0026] Optionally, the cobalt salt is cobalt nitrate.

[0027] Optionally, in step (c), the mass ratio of the precursor powder to the volume ratio of the organic solution is 1 g: (150-350) mL.

[0028] Optionally, in step (c), the mass ratio of the precursor powder to the volume ratio of the organic solution is selected from any ratio of 1g:150mL, 1g:250mL, 1g:350mL, or any value between two ratios.

[0029] Optionally, the total concentration of iron and cobalt in the organic solution is 0.1 to 5 mg / mL, wherein the iron and cobalt are expressed by their own elemental mass.

[0030] Optionally, the total concentration of iron and cobalt in the organic solution is selected from any value or a range between 0.1 mg / mL, 1 mg / mL, 3 mg / mL, 4 mg / mL, and 5 mg / mL.

[0031] Optionally, in the organic solution, the molar ratio of iron salt to cobalt salt is 1:(1-3), wherein the molar amounts of iron and cobalt are expressed in terms of the amount of iron and cobalt.

[0032] Optionally, in the organic solution, the molar ratio of iron salt to cobalt salt is selected from any ratio of 1:1, 1:2, 1:3 or a range between two ratios.

[0033] Optionally, in step (a), the volume of the styrene, the mass of the initiator, and the mass ratio of the stabilizer are 1 mL: (10-20) mg: (20-40) mg.

[0034] Optionally, in step (a), the volume of styrene, the mass of the initiator, and the volume ratio of the stabilizer are selected from any ratio or a range between two values ​​from 1 mL: 10 mg: 20 mg, 1 mL: 12 mg: 34 mg, 1 mL: 15 mg: 37 mg, and 1 mL: 20 mg: 40 mg.

[0035] Optionally, the concentration of the polystyrene spherical emulsion is 0.1 to 0.3 g / mL.

[0036] Optionally, the concentration of the polystyrene spherical emulsion is selected from any value of 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, or a range between two values.

[0037] Optionally, in step (b), the volume ratio of the polystyrene spherical emulsion to the zinc salt is 1 mL: (100-200) mg.

[0038] Optionally, in step (b), the volume ratio of the polystyrene spherical emulsion to the zinc salt is selected from any value or a range between 1 mL: 100 mg, 1 mL: 125 mg, 1 mL: 150 mg, 1 mL: 175 mg, and 1 mL: 200 mg.

[0039] Optionally, in step (b), the volume ratio of the polystyrene spherical emulsion to the mass ratio of dimethylimidazole is 1 mL: (100-300) mg.

[0040] Optionally, in step (b), the volume ratio of the polystyrene spherical emulsion to the dimethylimidazole is any ratio or a range between two ratios of 1 mL: 100 mg, 1 mL: 150 mg, 1 mL: 200 mg, 1 mL: 250 mg, or 1 mL: 300 mg.

[0041] Optionally, in step (a), the polymerization reaction conditions are: a reaction temperature of 90–100°C and a reaction time of 20–30 h.

[0042] Optionally, in step (a), the reaction temperature of the polymerization reaction is selected from any value of 90°C, 92°C, 95°C, and 100°C, or a range between two values.

[0043] Optionally, in step (a), the reaction time of the polymerization reaction is selected from any value of 20h, 24h, 25h, 30h or a range between two values.

[0044] Optionally, in step (b), the reaction temperature is 20–30°C, and the reaction time is 1–3 hours.

[0045] Optionally, in step (b), the temperature of the reaction is selected from any value of 20°C, 25°C, 30°C, or a range between two values.

[0046] Optionally, in step (b), the reaction time is selected from any value of 1h, 2h, 3h or a range between two values.

[0047] Optionally, in step (b), the drying temperature is 60–80°C and the drying time is 5–10 hours.

[0048] Optionally, in step (b), the drying temperature is selected from any value of 60°C, 70°C, or 80°C, or a range between two values.

[0049] Optionally, in step (b), the drying time is selected from any value of 5h, 7h, 10h or a range between two values.

[0050] Optionally, in step (c), the calcination conditions are: under an argon atmosphere, the heating rate is 1℃ / min to 5℃ / min, the calcination temperature is 700℃ to 1000℃, and the calcination time is 90 to 160 min.

[0051] Optionally, the heating rate of the calcination is selected from any value or a range between two values ​​of 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, and 5℃ / min.

[0052] Optionally, the calcination temperature is selected from any value of 700℃, 800℃, 900℃, 1000℃ or a range between two values.

[0053] Optionally, the calcination time is selected from any value of 90 min, 120 min, or 160 min, or a range between two values.

[0054] Optionally, in step (c), the immersion temperature is 20–30°C and the immersion time is 20–40 h.

[0055] Optionally, in step (c), the immersion temperature is selected from any value of 20°C, 25°C, or 30°C, or a range between two values.

[0056] Optionally, in step (c), the immersion time is selected from any value of 20h, 30h, 40h or a range between two values.

[0057] According to another aspect of this application, a cathode catalyst is provided, comprising the above-described catalyst or a catalyst prepared according to the above-described preparation method, thereby improving the performance of the battery.

[0058] Optionally, the cathode catalyst is used in electrochemical energy storage and conversion.

[0059] The beneficial effects that this application can produce include:

[0060] 1) The three-dimensional macroporous redox catalyst provided in this application exhibits excellent oxygen reduction performance, with an oxygen reduction half-wave potential of 0.901 V in 0.1 mol / L potassium hydroxide solution and an oxygen reduction mottled potential of 0.806 V in 0.5 mol / L sulfuric acid solution. Compared to noble metal catalysts, this oxygen reduction catalyst is a non-noble metal oxygen reduction catalyst, which reduces costs while exhibiting catalytic performance comparable to that of noble metal catalysts.

[0061] 2) The preparation method provided in this application has low catalyst production cost, simple process, and high yield. Attached Figure Description

[0062] Figure 1This is a schematic diagram illustrating the preparation method of the three-dimensional macroporous oxygen reduction catalyst in Example 1 of this application;

[0063] Figure 2 The image shows the XRD pattern of the three-dimensional macroporous oxygen reduction catalyst precursor in Example 2 of this application.

[0064] Figure 3 The image shows the XRD pattern of the three-dimensional macroporous oxygen reduction catalyst in Example 2 of this application.

[0065] Figure 4 This is a cyclic voltammetry curve of alkaline oxygen reduction using the three-dimensional macroporous oxygen reduction catalyst in Example 3 of this application;

[0066] Figure 5 This is a cyclic voltammetry curve of the acidic oxygen reduction catalyst in Example 4 of this application;

[0067] Figure 6 This is a linear scanning curve of the three-dimensional macroporous oxygen reduction catalyst and the 20% platinum-carbon basic oxygen reduction catalyst in Example 3 of this application;

[0068] Figure 7 This is a linear scanning curve of the three-dimensional macroporous oxygen reduction catalyst and the oxygen reduction of 20% platinum carbonate in Example 4 of this application. Detailed Implementation

[0069] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0070] Unless otherwise specified, the raw materials and reagents used in the embodiments of this application were all purchased commercially.

[0071] The analysis method in the embodiments of this application is as follows:

[0072] The samples were characterized by scanning electron microscopy (SEM) using a JSM6700-F field emission scanning electron microscope.

[0073] Cyclic voltammetry and polarization curve analysis of the electrodes were performed on a CHI760E electrochemical workstation from Shanghai Chenhua Co., Ltd.

[0074] like Figure 1 As shown, the inventive concept of this application is as follows:

[0075] Step 1: First, add the PS (polystyrene spheres) and Zn... 2+ The mixture of zinc ions and 2-MIN (dimethylimidazole) was reacted and crystallized to prepare 3DM-ZIF-8@PS (metal-organic framework compound supported on polystyrene spheres);

[0076] Step 2: After washing away the PS loaded in 3DM-ZIF-8@PS, iron and cobalt elements are loaded to obtain 3DM-FeCo-ZIF-8 (a metal-organic framework compound loaded with iron and cobalt ions);

[0077] Step 3: Carbonize 3DM-FeCo-ZIF-8 to obtain FeCo-3DMNC (a catalyst with iron and cobalt metal supported on porous carbon material).

[0078] Example 1: Preparation of Three-Dimensional Macroporous Oxygen Reduction Catalyst

[0079] The method for preparing the catalyst includes the following steps:

[0080] (1) Add 30 mL of styrene and 1.02 g of polyvinylpyrrolidone initiator to 240 mL of deionized water and purge with argon gas for 20 minutes. Then, reflux and stir in an oil bath at 92 °C for 40 minutes. Next, add 36 mL of an aqueous solution containing 0.364 g of potassium persulfate and polymerize for 24 hours. Concentrate the obtained polystyrene spherical emulsion to 120 mL. The concentration of the concentrated polystyrene spherical emulsion is 0.2 g / mL.

[0081] (2) Mix 20 mL of the polystyrene sphere emulsion obtained in step (1) with 3 g of zinc nitrate hexahydrate, then add 20 mL of an aqueous solution containing 4 g of dimethylimidazole, and stir at room temperature for 2 hours. Collect the metal-organic framework compound loaded with polystyrene spheres by centrifugation, remove the polystyrene spheres with dimethylformamide, wash, and dry at 70 °C for 7 hours to obtain the precursor powder.

[0082] (3) 200 mg of the precursor powder obtained in step (2) was placed in 50 mL of methanol containing 50 mg of ferric nitrate nonahydrate and 50 mg of cobalt nitrate hexahydrate and soaked for 36 hours. The precursor was then collected and washed with ethanol and deionized water and dried at 60 °C to obtain a precursor powder loaded with iron and cobalt elements. The iron loading amount in the precursor powder loaded with iron and cobalt elements was 2% and the cobalt loading amount was 0.5%.

[0083] (4) The precursor powder obtained in step (3) is placed in a corundum ceramic boat and placed in a tube furnace. Under an argon atmosphere, the temperature is increased from room temperature to 900°C at a heating rate of 5°C / min and held for 2 hours. Then it is naturally cooled to room temperature to obtain the three-dimensional macroporous oxygen reduction catalyst.

[0084] Example 2 Characterization of three-dimensional macroporous oxygen reduction catalyst

[0085] The morphology of the three-dimensional macroporous oxygen reduction catalyst precursor and the micronized three-dimensional macroporous oxygen reduction catalyst sample obtained in Example 1 was examined using scanning electron microscopy (SEM). The SEM images are shown below. Figure 1 As shown. Figure 2XRD analysis showed that the precursor was a metal-organic framework compound. For example... Figure 3 As shown in the XRD pattern, no obvious metal peaks were observed in the three-dimensional macroporous oxygen reduction catalyst, indicating that no obvious metal particles were formed in the catalyst.

[0086] Example 3: Electrochemical testing of a three-dimensional macroporous oxygen reduction catalyst for alkaline oxygen reduction.

[0087] The three-dimensional macroporous oxygen reduction catalyst obtained in Example 1 and 20% platinum-carbon were each 3 mg and added to 10 μL of Nafion, 60 μL of ethanol, and 30 μL of deionized water, respectively, and dispersed uniformly by ultrasonication for 30 minutes. 6 μL of each ultrasonic dispersion was drop-coated onto a rotating disk electrode, and cyclic voltammetry and linear sweep voltammetry (LSV) were performed on an electrochemical workstation using a 0.1 mol / L potassium hydroxide solution to test the alkaline oxygen reduction reaction performance.

[0088] like Figure 4 , 6 This indicates that the three-dimensional macroporous oxygen reduction catalyst exhibits superior oxygen reduction activity under alkaline conditions compared to 20% platinum-carbon, with a half-wave potential of 0.901 V.

[0089] Example 4: Electrochemical testing of three-dimensional macroporous oxygen reduction catalyst for acidic oxygen reduction.

[0090] The three-dimensional macroporous oxygen reduction catalyst obtained in Example 1 and 20% platinum-carbon were each 3 mg and added to 10 μL of Nafion, 60 μL of ethanol, and 30 μL of deionized water, respectively, and dispersed uniformly by ultrasonication for 30 minutes. 6 μL of each ultrasonic dispersion was drop-coated onto a rotating disk electrode, and cyclic voltammetry and linear sweep voltammetry (LSV) were performed on an electrochemical workstation using a 0.5 mol / L sulfuric acid solution to test the performance of the acidic oxygen reduction reaction.

[0091] like Figure 5 , 7 This indicates that the three-dimensional macroporous oxygen reduction catalyst also exhibits excellent oxygen reduction activity under acidic conditions, with a half-wave potential of 0.806V.

[0092] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and all fall within the scope of the technical solution.

Claims

1. A three-dimensional macroporous oxygen reduction catalyst, characterized in that, It includes porous carbon materials and active components, wherein the active components are loaded on the porous carbon materials; The active component includes active elements, which include iron and cobalt, wherein both iron and cobalt are dispersed at the atomic level. The catalyst has a porous pebble-like structure in its microstructure. The catalyst is formed by removing the polystyrene spheres from a metal-organic framework compound loaded with polystyrene spheres, impregnating it with the loaded iron and cobalt, and then carbonizing it. The metal-organic framework compound is ZIF-8.

2. The catalyst according to claim 1, characterized in that, In the catalyst, the mass fraction of iron is 0.1% to 5%, and the mass of iron is expressed as the mass of iron element. In the catalyst, the mass fraction of cobalt is 0.1% to 5%, and the mass of cobalt is expressed as the mass of cobalt element.

3. The catalyst according to claim 1, characterized in that, The catalyst has a particle size of 2.0~3.0μm; The porous carbon material includes nitrogen and carbon elements.

4. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that, Includes the following steps: (a) Polymerize a mixture containing styrene, an initiator, and a stabilizer to obtain a polystyrene spherical emulsion; (b) The polystyrene ball emulsion obtained in step (a), zinc salt, and dimethylimidazole are mixed, reacted, and centrifuged to obtain a metal-organic framework compound loaded with polystyrene balls. The polystyrene balls are then removed by washing with a washing solvent and dried to obtain a precursor powder. (c) The precursor powder obtained in step (b) is added to an organic solution containing iron salt and cobalt salt, impregnated, and calcined to obtain the catalyst.

5. The preparation method according to claim 4, characterized in that, The initiator is selected from at least one of potassium persulfate, sodium persulfate, and ammonium persulfate; The stabilizer is selected from at least one of polyvinylpyrrolidone, polyacrylic acid, and nonionic cellulose; The organic solution also includes an organic solvent, which is selected from at least one of methanol, ethanol, and cyclohexane; The washing solvent is selected from at least one of dimethylformamide and tetrahydrofuran; The zinc salt is selected from zinc nitrate and zinc acetate; The iron salt is a soluble iron salt; The cobalt salt is a soluble cobalt salt.

6. The preparation method according to claim 5, characterized in that, The iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric sulfate, and ferric acetylacetone; The cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetylacetonate.

7. The preparation method according to claim 5, characterized in that, The iron salt is ferric nitrate.

8. The preparation method according to claim 5, characterized in that, The cobalt salt is cobalt nitrate.

9. The preparation method according to claim 4, characterized in that, In step (c), the mass ratio of the precursor powder to the volume ratio of the organic solution is 1 g: (150~350) mL; The total concentration of iron and cobalt in the organic solution is 0.1~5 mg / mL, and the iron and cobalt are expressed as their own elemental mass. In the organic solution, the molar ratio of iron salt to cobalt salt is 1:(1~3), where the molar amounts of iron and cobalt are expressed as follows; In step (a), the volume of styrene, the mass of the initiator, and the mass ratio of the stabilizer are 1 mL : (10~20) mg : (20~40) mg; The concentration of the polystyrene spherical emulsion is 0.1~0.3 g / mL; In step (b), the volume ratio of the polystyrene spherical emulsion to the zinc salt is 1 mL: (100~200) mg; In step (b), the volume ratio of the polystyrene spherical emulsion to the mass ratio of dimethylimidazole is 1 mL: (100~300) mg.

10. The preparation method according to claim 4, characterized in that, In step (a), the conditions for the polymerization reaction are: reaction temperature of 90~100℃ and reaction time of 20~30h; In step (b), the reaction temperature is 20~30℃ and the reaction time is 1~3h; In step (b), the drying temperature is 60~80℃ and the drying time is 5~10h.

11. The preparation method according to claim 4, characterized in that, In step (c), the calcination conditions are: under an argon atmosphere, the heating rate is 1℃ / min~5℃ / min, the calcination temperature is 700~1000℃, and the calcination time is 90~160min; In step (c), the immersion temperature is 20~30℃ and the immersion time is 20~40h.

12. A cathode catalyst, characterized in that, The cathode catalyst comprises the catalyst according to any one of claims 1 to 3 or the catalyst obtained by the preparation method according to any one of claims 4 to 11.

13. A cathode catalyst according to claim 12, characterized in that, Applications in electrochemical energy storage and conversion.

Citation Information

Patent Citations

  • Preparation method and application of Fe and Co bimetallic doped mesoporous carbon oxygen reduction catalyst

    CN113013428A